Non-conforming FEM-FEM coupling approaches and their application to dynamic structural analysis. (15th August 2021) - Wilson, Peter; Teschemacher, Tobias; Bucher, Philipp; Wüchner, Roland
Highlights: Application of partitioned dynamic structural finite element analysis. Stability and accuracy evaluation of non-conforming FEM-FEM coupling technologies. Comparison of Gauss–Seidel and FETI-based FEM-FEM coupling approaches. Effect of origin/destination designation on FETI-based coupling. Partitioned coupling approaches computationally competitive with monolithic solution. Abstract: Contrasting monolithically solved numerical analyses, partitioned coupled simulations confer the substantial advantages of software modularity, employing the best numerical techniques for each domain and readiness to extend the coupling to other physics and emerging numerical techniques. However, an additional interface problem is created and must be solved without significantly deteriorating solution accuracy. This application-oriented study examines non-conforming partitioned dynamic FEM-FEM simulations under approaches of varying complexity illustrating their ranges of applicability as well as key advantages and disadvantages. After presenting the pertinent aspects of popular coupling technologies, two numerical examples of different complexities are considered. Although the efficiently simple Gauss–Seidel approach is suitable for partitioned systems of dissimilar stiffnesses, such as structure and fluid/soil interaction, stability and accuracy deteriorate as domain compliances align rendering it unsuitable for partitioned structural analysis. Contrasting this, the more robust FETI-based method maintains stability over all stiffness ratios and demonstrates excellent agreement with equivalent monolithic structural responses in terms of displacements and stresses.